OPTIMASI PORTOFOLIO SAHAM MNC36 MENGGUNAKAN METODE MARKOWITZ - Gustina K. S, Annisa Hevita; Dewi, Karina Sylfia; Baiti, Putri Isnaini Cahyaning; Azzanina, Nanda (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study is to determine the stocks listed in MNC36 for the period April 2024 to February 2025 that are included in the optimal portfolio according to the Markowitz Model. Data analysis was carried out using the Markowitz Model stages which began by collecting closing stock price data until obtaining the optimal portfolio. Based on the results of the analysis that has been carried out, there are 8 stocks that have positive returns and its expected risk less than its expected return, namely BRIS, BRMS, EXCL, HEAL, ICBP, INDF, MTEL, MYOR. After that, a combination of two stocks were proportioned from the 8 stocks before. Therefore, the optimal combination of two stocks was determined: BRIS with fund allocation of 31% and INDF’s capital allocation of 69%. Penelitian ini bertujuan untuk mengidentifikasi saham–saham yang terdaftar dalam MNC36 periode April 2024 sampai dengan Februari 2025 yang dapat dimasukkan dalam portofolio optimal berdasarkan Model Markowitz. Analisis data dilakukan melalui tahapan Model Markowitz, dimulai dengan pengumpulan data harga saham penutupan hingga diperoleh portofolio yang optimal. Berdasarkan hasil analisis yang telah dilakukan, terdapat 8 saham yang memiliki return positif dan nilai expected risk yang lebih kecil dari expected return yaitu BRIS, BRMS, EXCL, HEAL, ICBP, INDF, MTEL, MYOR. Kemudian dilakukan pembobotan saham antara kombinasi dua saham dari ke-8 saham tersebut. Sehingga didapatkan kombinasi optimal dari dua saham yaitu BRIS dengan alokasi dana sebesar 31% dan INDF sebesar 69%.